Upaya Eskalasi Keterampilan Komunikasi Peserta Didik Melalui Kombinasi Metode Gallery Walk dan Flipped Classroom Collaborative Learning - Emir Surya Kautsar; Andi Rahmat Saleh; Roni Wahyuda (RAYHAN INTERMEDIA, 2023)
This research aims to examine the escalation of communication skills (oral, written, and interpersonal) of Biology students through the implementation of a combination of the gallery walk and flipped classroom collaborative learning method in Grade XI Science Program 3 of SMAN 13 Makassar for the academic year 2022/2023. This study adopts collaborative classroom action research and is conducted over two research cycles. The research design follows a gradual lesson study approach from one cycle to the next. The stages within one cycle include planning, implementation, observation, and reflection. Data collection techniques involve observation sheets and documentation to observe students' communication skills during the learning process. Three observers were involved in the study. The collected data is analyzed using quantitative descriptive analysis. The average cumulative communication skills at the beginning of the cycle were 64.83%, which increased to 77.21% by the end of the first cycle and further improved to 89.96% by the end of the second cycle. The overall improvement from the intervention until the end of the second cycle amounted to 25.13%. The findings of this research indicate that the implementation of a combination of the gallery walk and flipped classroom collaborative learning method effectively enhances the communication skills of students in Grade XI Science Program 3 of SMAN 13 Makassar for the academic year 2022/2023.